A Dye-Sensitized Solar Cell Using a Composite of PEDOT:PSS and Carbon Derived from Human Hair for a Counter Electrode - Klitsada Moolsarn; Apishok Tangtrakarn; Adulphan Pimsawat; Kornrawit Duangsa; Charusporn Mongkolkachit; Wasan Maiaugree; Vittaya Amornkitbamrung (International Journal of Photoenergy)
Carbon derived from hair is interesting because it has good electrocatalytic activity due to the existence of innate heteroatom dopants especially nitrogen and sulfur. In this study, a carbon catalyst containing high nitrogen contents (9.47 at.%) was fabricated without using any harsh chemicals. Moreover, the carbonization temperature was only 700°C. Carbonized hair/PEDOT:PSS composites (CxP) with varied carbon contents from x = 0.2 to 0.8 g were tested as a counter electrode (CE) for a dye-sensitized solar cell (DSSC). This type of DSSC CE has scarcely been investigated. A DSSC with a C0.6P CE provides the best efficiency (6.54 ± 0.11%) among all composite CEs because it has a high fill factor (FF) and a high short-circuit current density (Jsc). The efficiency of DSSC with C0.6P CE is lower than Pt’s (7.29 ± 0.01%) since the Pt-based DSSC has higher FF and Jsc values. However, C0.6P is still promising as a DSSC CE since it is more cost-effective than Pt.